Typological Features of Circulation in Anemic Animals During Infusion Therapy and Hyperbaric Oxygenation - Yu. M. Tumanovsky; G. Yu. Savina (Общая реаниматология)
Objective: to study systemic hemodynamic changes, by taking into account the typological features of a blood circulatory device in anemic animals when therapeutic measures were implemented.Materials and methods. Experiments were made on 58 dogs in 3 series of experiments: 1) 20 animals under hemorrhagic shock (a control group); 2) 18 anemic animals receiving further infusion therapy; and 3) 20 anemic animals exposed to hyperbaric oxygenation (HBO) (pO2 = 300 kPa; 60-min session). In each series, animals with eukinetic, hypokinetic, and hyperkinetic circulations were identified. Cardiac and stroke indices (CI and SI), left ventricular stroke output index (LVSOI), specific peripheral vascular resistance (SPVR), double product (DP), heart rate, and blood pressure (BP) were determined at the baseline, at 30- and 90-minute shock and after treatment.Results. In the late posthemorrhagic period (at min 90), the preferential preponderance of hyperkinetic circulation in untreated animals in the late stage was characterized by the exhaustion of cardiovascular compensatory reactions and attended by a reduction in BP and central hemodynamic parameters (CI, SI, LVSOI) and evolving tachycardia. In the animals with all typological groups, infusion therapy produced a short-term impact on the activation of compensatory hemodynamic reactions, by increasing vascular tone with relatively low baseline central hemodynamic values, which was due to the fact that the heart was overloaded with the excess volume of an infusion mixture and myocardial contractility was diminished. Under HBO, recovery of the baseline ratio of circulatory types increased cardiac functional reserves and eliminated myocardial hypoxia (DP normalization).Conclusion. In hypoxia, recovery of hemodynamic homeostasis in anemic animals is determined by the optimization of adaptive functional mechanisms responsible for circulatory regulation.